Radiation self absorption effect in Ar gas NX2 Mather type plasma focus - Ali, Z.; Lee, S.; Ismail, F. D.; Saktioto; Ali, J.; Yupapin, P. P. (My University, 2011)
The effect of self absorption becomes significant when plasma is dense enough to behave as optically thick. It is essential to account for the effect of self-absorption in that case. The variation of radial trajectory is investigated in this paper. In order to analyze the effect of self absorption of line radiation is investigated in argon plasma by observing the influence of pressure variation of gas. On comparison of the results of numerical experiment considering both aspects i.e. by including and excluding the self absorption term in Lee code an obvious deviation between the trajectories is observed. Last few fractions of seconds (200-300 ns) corroborated the slow compression phase. Results with self absorption showed the compression levels off while without self absorption radiative collapse was observed due to radiative cooling. Due to self absorption the absorbed radiation kept the plasma from radiative collapse turning the results to be more realistic.
Keywords: Dense Plasma Focus; Radiation Cooling; Self Absorption; Slow Compression Phase